DIGITALIZATION AS A NEW ENVIRONMENTAL EXPOSURE FACTOR: THE IMPACT OF INFORMATION OVERLOAD ON HUMAN NERVOUS AND IMMUNE SYSTEM FUNCTIONS - Monika Czekalska; Patrycja Jędrzejewska Rzezak; Luiza Łabuzińska; Monika Kulińska; Monika Wandasiewicz; Dominika Żukowiecka Sęga; Konrad Czchowski; Klaudia Lipińska; Aleksandra Winsyk; Kinga Knutelska (International Journal of Innovative Technologies in Social Science, 2025)
The increasing digitization of everyday life is associated with the increasing exposure of the population to informational, sensory, and social stimuli originating from screen devices and digital media. The digital environment is not a classically understood environmental factor; its impact on the body exhibits characteristics of a chronic stressor, affecting the functions of the neuroimmunoendocrine axis, neuroplasticity processes, and the regulation of the immune response. The aim of this study was to review current data on the impact of information overload and digital overstimulation on the human nervous and immune systems, as well as to assess the validity of considering the digital environment as a new form of environmental exposure in the context of public health. Research published between 2018 and 2025 in the PubMed, Scopus, and Web of Science databases was analyzed. This included: population based correlation studies between screen time and markers of stress and inflammation, fMRI studies illustrating changes in brain structure and function during digital overload, animal models examining the effects of sensory overstimulation on the HPA axis and immunity, and randomized intervention trials on reducing screen time. The review found consistent evidence of chronic activation of the HPA axis under digital stress, leading to elevated cortisol levels, impaired neurogenesis, and decreased parasympathetic activity. Brain changes are also observed that correlate with symptoms of depression, insomnia, and attention deficits. Reduced immunity and increased inflammatory markers were demonstrated. Interventions limiting digital exposure resulted in significant reductions in cortisol and CRP levels. The digital environment meets the criteria for an environmental stressor with a real impact on the nervous and immune systems. Digital hygiene should become an integral component of public health strategies, prevention, and the design of work and learning environments.